Adaptation of an acoustic propagation model to the parallel architecture of a graphics processor - Ey, Emanuel (2014)
High performance underwater acoustic models are of great importance for enabling real-time acoustic source tracking, geoacoustic inversion, environmental monitoring and high-frequency underwater communications. Given the parallelizable nature of raytracing, in general, and of the ray superposition algorithm in particular, use of multiple computing units for the development of real-time e cient applications based on ray tracing is becoming of extreme importance.